Strategi keberlanjutan social enterprise - Hani Purnawanti; Maria R. Nindita Radyati; Maria Ariesta Ulfa (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2022)
Abstract This study aims to analyze the strategy of social enterprise sustainability. This type of research is qualitative research. The object of this research is PT X with a total of 13 stakeholders as resource persons. Data collection using in-depth interview techniques. The analysis method uses content analysis. The findings are that businesses are run with social innovation and operating practices that are in line with sustainable development goals, although there are internal business challenges related to errors in governance, improvements are made through improving governance and focusing on social innovation, developing partnerships with communities and consumers in produce service products while solving social problems as well as being able to positively increase finances. The owner who is also the manager has applied the concept of an entrepreneurial cycle that is able to become a major factor in creating PT X's business sustainability. Research contributions to the SDG's are related to quality education (SDG’s 4), Decent work & economic growth (SDG's 8), infrastructure, industry & innovation (SDG's 9) and partnerships to achieve goals (SDG's17) and implement some of the provisions of international standards in ISO 26000 Keywords: Social Enterprise, Social Innovation, Community Involvement, Transformational Leadership Abstrak Penelitian bertujuan menganalisis strategi keberlanjutan social enterprise. Jenis penelitian ini adalah penelitian kualitatif. Obyek penelitian ini adalah PT X dengan total narasumber stakeholder sebanyak 13 orang. Pengumpulan data menggunakan tehnik wawancara mendalam. Metode analisis menggunakan analisa konten. Hasil temuan yaitu usaha yang dijalankan dengan inovasi sosial dan praktek operasi yang sejalan dengan dengan tujuan pembangunan berkelanjutan, meskipun terdapat tantangan bisnis internal terkait kekeliruan dalam tata kelola namun dilakukan pembenahan melalui perbaikan tata kelola serta fokus dalam inovasi sosial, mengembangkan kemitraan dengan komunitas dan konsumen dalam menghasilkan produk layanan sekaligus memecahkan masalah sosial serta mampu meningkatkan keuangan secara positif. Pemilik yang juga sebagai pengelola telah menerapkan konsep siklus kewirausahaan yang mampu menjadi faktor utama dalam menciptakan keberlanjutan bisnis PT X. Kontribusi penelitian pada SDG's terkait pendidikan bermutu (SDGs 4), Pekerjaan layak & pertumbuhan ekonomi (SDG's 8), infrastruktur, industri & inovasi (SDG's 9) dan kemitraan untuk mencapai tujuan (SDG's17) serta menerapkan sebagian ketentuan standar internasional dalam ISO 26000.